2008
DOI: 10.1161/circulationaha.107.748053
|View full text |Cite
|
Sign up to set email alerts
|

Differential Behaviors of Atrial Versus Ventricular Fibroblasts

Abstract: Background-In various heart disease paradigms, atria show stronger fibrotic responses than ventricles. The possibility that atrial and ventricular fibroblasts respond differentially to pathological stimuli has not been examined. Methods and Results-We compared various morphological, secretory, and proliferative response indexes of canine atrial versus ventricular fibroblasts. Cultured atrial fibroblasts showed faster cell surface area increases, distinct morphology at confluence, and greater ␣-smooth muscle ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(103 citation statements)
references
References 52 publications
6
97
0
Order By: Relevance
“…Although it has been reported that the atrium is more susceptible to fibrotic changes than the ventricle, 16 the precise mechanisms are still unknown. It has been shown that the plasma level of NOx, an NO metabolite, was significantly decreased in AF patients 17 and that AF was associated with a marked decrease in eNOS protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that the atrium is more susceptible to fibrotic changes than the ventricle, 16 the precise mechanisms are still unknown. It has been shown that the plasma level of NOx, an NO metabolite, was significantly decreased in AF patients 17 and that AF was associated with a marked decrease in eNOS protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly important component is atrial fibrosis, which in experimental models occurs earlier in the course of CHF, and to a much greater extent, than in the ventricles, at least in part because of atrial-ventricular fibroblastphenotype differences. 4 Congestive heart failure-related fibrosis slowly, if at all, and the AFpromoting substrate predominantly tracks fibrosis rather than other components of atrial remodelling like ion-current or connexin changes. Unlike the case for AF-induced remodelling, the atrial ion-current changes in CHF do not abbreviate APD or cause overall conduction slowing, 113,114 so they do not contribute directly to arrhythmogenesis.…”
Section: Atrial Cardiomyopathy Due To Congestive Heart Failurementioning
confidence: 99%
“…TGF-β 1 , secreted by both fibroblasts and cardiomyocytes, is an important profibrotic mediator (119). Cardiac overexpression of constitutively active TGF-β 1 causes selective atrial fibrosis, conduction heterogeneity, and AF susceptibility (120).…”
Section: Heart Disease-related Atrial Fibrosismentioning
confidence: 99%
“…Cardiac overexpression of constitutively active TGF-β 1 causes selective atrial fibrosis, conduction heterogeneity, and AF susceptibility (120). TGF-β 1 functions as a downstream mediator of Ang II in both paracrine and autocrine ways (119). It acts primarily through the SMAD pathway to stimu-…”
Section: Heart Disease-related Atrial Fibrosismentioning
confidence: 99%